ACTR-20. EFFICACY OF INITIAL TEMOZOLOMIDE FOR HIGH-RISK LOW GRADE GLIOMAS IN A PHASE II AINO (ITALIAN ASSOCIATION FOR NEURO-ONCOLOGY) STUDY: A POST-HOC ANALYSIS WITHIN MOLECULAR SUBGROUPS OF WHO 2016. (11th November 2019) - Rudà, Roberta; Pellerino, Alessia; Pace, Andrea; Maria Carapella, Carmine; Dealis, Cristina; Caroli, Manuela; Faedi, Marina; Bello, Lorenzo; Migliore, Enrica; Marchese, Giulia; Bertero, Luca; Cassoni, Paola; et al.
Abstract: BACKGROUND: The optimal management of high risk WHO grade II gliomas after surgery is still debated. The efficacy of initial temozolomide to delay radiotherapy and risk of cognitive defects could vary across the molecular subgroups of WHO 2016, but information on this issue are lacking. PATIENTS AND METHODS: A post-hoc analysis has been performed on a cohort of high risk WHO grade II gliomas, who received initial temozolomide alone in phase II multicenter study, with the objective of re-evaluating the long-term results across the different molecular subgroups of the WHO 2016 classification. The primary endpoint of the study, carried out between 2007 and 2010, was response rate according to RANO, being seizure response, PFS and OS secondary endpoints. RESULTS: Response rate (partial and minor responses) among oligodendrogliomas IDH-mutant and 1p/19q codeleted (76%) was significantly higher than that among diffuse astrocytomas either mutant (55%) or wild-type (36%). A reduction of seizure frequency >50% was observed in 87% patients and a seizure freedom in 72%. The probability of seizure reduction >50% was significantly associated with the presence of an IDH mutation. Median PFS, PFS at 5 and 10 years, median OS and OS at 5 and 10 years were all significantly longer in oligodendrogliomas IDH-mutant and 1p/19q codeleted. Of patients who did not recur or delay radiotherapy at recurrence for a median follow-up of 8.2 years, 67% and 59%, respectively, were oligodendrogliomas IDH-mutant and 1p/19q codeleted. CONCLUSIONS: The post-hoc analysis of this phase II trial suggests that the beneficial effects of initial temozolomide prevail in oligodendrogliomas IDH-mutant and 1p/19q codeleted: thus, these tumors, when incompletely resected or progressive after surgery, especially when suffering from pharmacoresistant seizures, could receive temozolomide as initial treatment with radiotherapy and chemotherapy at recurrence. The trial was registered with EU Clinical Trials Register, EudraCT n. 2007/000386-38.